REFLECȚII ASUPRA PROBLEMEI RĂULUI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Reflections on the Problem of EvilAs long as the evil together with the character that defines him, the Devil, cannot be known in other way, as Messadié says, than through the discourse, we are going to analyze some works in which the devil is mentioned. First of all, we are not investigating a historical event or action, but rather a renowned and over discussed topic. Therefore, the itinerary of our investigation will consider important works that have been written on this subject, starting, as we said, with the important writings, which are fundamental for the universal cultural area. Without claiming to exhaust or even cover this topic, we will review the essential contributions to the evil’s problem: mythological and theological analyses, philosophical reflections, historical documentation, sociological and anthropological approaches, psychological judgments and, of course, the inexhaustible literary realm or revaluation of evil in the space of literary fiction.